The simultaneous determination of capsaicinoids, tocopherols, and carotenoids in pungent pepper powder. Issue 4 (25th February 2017) - Nagy, Zsuzsa; Daood, Hussein; Koncsek, Arnold; Molnár, Helga; Helyes, Lajos
ABSTRACT: From nutritional points of view, carotenoids, capsaicinoids, and tocopherols are valuable constituents in pungent peppers. A rapid and reliable high performance liquid chromatography (HPLC) method for the simultaneous determination of phytonutrients in spice red peppers and chili products was developed and validated. The method included simultaneous detection by fluorescence and diode-array detectors. The major capsaicinoids, two tocopherols and 43 carotenoid components, were simultaneously separated, detected, and identified in the appointed pepper powder (containing Capsicum annuum and Capsicum frutescens ) for method validation. The separation was performed on a Nucleosil C18 reverse phase column and optimized gradient elution. Resolution ranged between 0.96 and 1.46 with the highest values corresponding to γ-tocopherol and α-tocopherol. The limits of detection and quantification of target compounds ranged between 18.77 and 148.08 ng mL −1 . Recoveries were between 89.83–100.26 and 79.72–88.86% when standard materials were spiked at low and high amounts, respectively. The most sufficient extraction of the different phytonutrients was achieved by mixture of methanol and acetone, although it was only slightly better than the mixture of methanol and acetonitrile. These results suggest that the developed method could be used for rapid, one-step determination of a wide range of phytonutrients in chili and pepper powders. GRAPHICAL ABSTRACT: